Black Women Reporting and Seeking Help for Sexual Assault: A Call for Action - Hart, Maya; Jackson, Mary S. (International Journal of Criminology and Sociology, 2023)
Black women in America have historically been victims of oppression, racism, and sexual assault. This victimization can be traced as far back as the forced immigration to America in Jamestown, Virginia in 1619. Forced travel bondage on slave ships highlights the institutionalized pattern, not only of their suffering from repeated rape, but also logs their victimized sufferings in silence that they had to endure then and continue to endure in 21st century contemporary America. Black women have been socialized intergenerationally to respond in a specific manner similar to the female slaves who endured rape from ship crew members during their long voyage to the Americas. Even after slavery was legally abolished in 1865, Black women continued to endure victimizations not only due to their gender, but also due to discrimination, classism, perceptions regarding their sexuality, racism, and fear. These intersectional factors cause Black women to have become unique experiences at the hands of rapists. Thus, Black women have unique experiences as victims of rape than other individuals who are also rape victims. Any discussion of Black women and rape must be placed in a sociohistorical framework. The purpose of this article is to revisit historical underpinnings about the rape of Black women in a socialized manner that continues to hinder a silent, nonactive role, and in some instances denial of being a victim of rape. The aim is to sensitize, stimulate, and motivate action by increasing social work classroom discussions about the topic, increasing research in the area of rape of Black women utilizing an intersectional approach reviewing factors that are unique to Black women, and providing more information as a resource to enhance community awareness. Effective intervention strategies are also delineated.